Raising Awareness of Environmental Crisis Caused by Textile Waste by Using 2-Dimentional Animation - Alia Amira Abd Rahman (Journal of Computing Technologies and Creative Content, 2025)
The environmental crisis resulting from textile waste has become a pressing issue in contemporary society. This study aims to explore the potential of 2-dimensional (2D) animation as a powerful medium for raising awareness and promoting sustainable practices in textile consumption. The abstract discusses the rationale, methodology, and key findings of the research project. The research begins by examining the alarming rise in textile waste and its detrimental impact on the environment, encompassing issues such as pollution, resource depletion, and greenhouse gas emissions. It further investigates the lack of public awareness regarding these consequences and emphasizes the need for effective communication strategies to address this issue. Drawing upon the principles of visual communication and storytelling, the research employs 2D animation to engage and educate audiences about the environmental implications of textile waste. By leveraging the creative potential of animation, the study develops a series of animated short films that vividly illustrate the life cycle of textiles, from production to disposal, highlighting the adverse effects at each stage. Through a combination of qualitative and quantitative research methods, the effectiveness of animated films in raising awareness and influencing attitudes towards sustainable textile consumption is assessed. Pre- and post-viewing surveys, focus groups, and interviews are conducted to measure the impact of the animation on viewers’ knowledge, perception, and behavioral intentions. The findings of the research reveal a significant positive correlation between exposure to animated films and increased awareness of the environmental crisis caused by textile waste. Participants reported heightened understanding of the issue, empathy towards the affected ecosystems, and a willingness to adopt more sustainable practices in their own textile consumption habits. This research contributes to the field by showcasing the power of 2D animation as an educational tool to address complex environmental challenges. The study highlights the importance of creative communication strategies in mobilizing public action and fostering a collective responsibility towards sustainable textile practices.